Ant algorithm for amplifier spontaneous emission (ASE)-aware routing - Chin, Tan Saw; Abbou, F. M.; Tat, Ewe Hong (IEICE-INST ELECTRONICS INFORMATION COMMUNICATIONS ENG, 2007)
In this paper, we propose and demonstrate an Ant-based constraint-based routing for transparent optical networks based on ASE noise accumulation along the lightpath. Our proposed algorithm selects the route based on the minimum ASE noise, leading to lower blocking probability. The numerical results show that the proposed algorithm outperforms the traditional shortest path routing algorithm. The results show that these ASE have a significant impact on transparent networks. Careful gain choice, low noise figure are strongly desired for the accomplishment of efficient, cost-effective, high capacity WDM transparent optical networks.